Behavior of closely spaced double-pile-supported jacket foundations for offshore wind energy converters. (June 2016) - Akdag, Cihan Taylan
Highlights: Large-scale field tests can be well simulated by numerical model. The efficiency of the method of stress extraction from interface elements to determine the soil reaction. The comparison of the behavior of the recommended closely spaced double-pile foundation system and conventional single pile foundation system. The effect of pile spacing and pile length on the behavior of closely spaced double-pile supported jacket foundation. Presentation of the effect of pile spacing and pile length on the load distribution. Abstract: As the offshore wind energy production units move to deeper waters the design of their foundations demand more creative and complex approaches especially for large turbines (i.e. ∼5–7 MW). In this article, a novel piled foundation alternative with closely spaced double piles at the edges of the jacket is studied for various pile spacing and lengths. A numerical parametric study was carried out to understand the effects of pile spacing and pile length on the behavior of the novel supporting system under monotonic combined loading in very dense sand. Prior to the analysis, the numerical model is validated in field tests with single-pile and double-pile configurations. The contribution of closely spaced double piles to the overall foundation response and load distribution among the piles were investigated. The response of the foundation was evaluated considering the horizontal load-head displacement, moment-head rotation, and initial stiffness of the soil-pile system. It is found that the response of the recommended foundation system is superior to that of a rather conventional system with single piles at the edges. The results indicate that the piles on the tension loading side evidently carried lower loads than those on the compression side. Moreover, the disposition of the piles is more important on the tension side, as the trailing piles carried considerably lower loads than the leading piles. It is found that the double pile system with a pile embedment length L / 2 and a pile spacing of S = 5 D, 6 D provides better response, where L is the embedded pile length of conventional system and D is the diameter of pile.